New records of crabs (Decapoda: Brachyura) from the New Zealand region, including a new species of Rochinia A. Milne-Edwards, 1875 (Majidae), and a revision of the genus Dromia Weber, 1795 (Dromiidae) - McLAY, COLIN L. (Zootaxa, 2009)
Seven species and two families previously unknown from New Zealand are recorded: Dynomene pilumnoides Alcock, 1900, Metadynomene tanensis (Yokoya, 1933) (Dynomenidae new to New Zealand); Pseudopalicus undulatus Castro, 2000 (Palicidae); Mursia microspina Davie & Short, 1989 (Calappidae new to New Zealand); Ovalipes elongatus Stephenson & Rees, 1968, Thalamita danae Stimpson, 1858, (Portunidae); Percnon planissimum (Herbst, 1804) (Plagusiidae); Ontogenetic morphological changes in Nectocarcinus antarcticus (Portunidae) are described. The southern limit for Pseudopalicus undulatus is extended from Fiji to New Zealand and the depth limit from 410 m to more than 560 m. A checklist of Brachyura recorded from the Kermadec Is is also updated. The genus Dromia Weber, 1795 (Dromiidae) is revised and restricted to the Atlantic Ocean (6 species) and Metadromia gen. nov. and Tumidodromia gen. nov., are erected for Indo-West Pacific species previously included in Dromia sensu lato. A new species of Rochinia (Epialtidae) is described from the Rumble V seamount. The stridulatory ridges on the chelipeds of Ocypode (Ocypodidae), important for identification, are shown to be sexually dimorphic: males have more striae than females. A single specimen of O. pallidula is reported from the Leigh Marine Reserve where it may have been accidentally released.